Slow relaxation of magnetization in unprecedented Cu–Ln-Rad hetero-tri-spin chains constructed from multidentate nitronyl nitroxide. Issue 29 (11th July 2019) - Sun, Juan; Sun, Zan; Wang, Kang; Xi, Lu; Ma, Yue; Li, Licun
Abstract : Unprecedented Cu–Ln heterometallic chains derived from poly-dentate nitronyl nitroxides are reported. A Tb complex shows slow magnetic relaxation, while a Dy derivative displays interesting two-step relaxations of magnetization. Abstract : Reactions of the radical 3, 5-bPy-Ph-Nit (2-[3, 5-bis(3-pyridyl)-phenyl]-4, 4, 5, 5-tetramethylimidazoline-1-oxyl-3-oxide) with Ln(hfac)3 and Cu(hfac)2 afforded four unprecedented radical-3d–4f chains with formula [Ln(hfac)3 ][Cu(hfac)2 ]2 (3, 5-bPy-Ph-Nit)(H2 O) n · n C7 H16 (Ln = Gd, 1 ; Tb, 2 ; Dy, 3 ; Ho, 4 ; hfac = hexafluoroacetylacetonate). In complexes1–4, each 3, 5-bPy-Ph-Nit radical serves as one μ4 -bridge to bind one Ln III ion and three Cu II ions via its two aminoxyl units and two pyridine-N atoms, giving rise to unique Cu–Ln-radical one-dimensional chains with a rare [Ln-NIT-Cu-NIT-Ln] structural motif. Magnetic investigation shows that ferromagnetic interactions are found between the aminoxyl unit and Cu(ii ) or Ln(iii ) ions. Interestingly, a Dy derivative displays two-step relaxations of magnetization, while a Tb complex exhibits field-induced slow magnetic relaxation, originating from the [Ln-NIT-Cu-NIT-Ln] ferromagnetic structural units.